Pengaruh penyerbukan antar spesies kopi yang dibudidayakan terhadap karakteristik buah dan biji: The effect of inter-pollination of cultivated coffee species on the characteristics of fruit and seeds - Dani, Dani; Rokhmah, Dewi Nur (Jurnal AGRO, 2025)
Interspecific pollination between Arabica coffee (Coffea arabica L.) and its diploid relatives are hypothesized to influence the resulting fruit and seed characteristics. To evaluate this effect, artificial interspecific pollination was conducted between C. arabica × C. canephora (A×C), C. arabica × C. liberica (A×L), and their reciprocals (C×A and L×A). As a control, intraspecific pollinations were also performed within C. arabica (A×A), C. canephora (C×C), and C. liberica (L×L). Morphometric traits observed included fruit weight, fruit length, fruit width, fruit thickness, fruit volume, number of seeds per fruit, and abnormalities in fruit and seed development. The mean values were statistically compared using t-tests. The results demonstrated that fruit weight and size from interspecific pollinations with maternal excess (A×C and A×L) were significantly smaller than those from intraspecific pollination within C. arabica. Fruit abnormalities, particularly the percentage of empty fruits, were markedly higher in interspecific combinations—regardless of whether maternal or paternal excess was involved—compared to intraspecific pollinations. However, no consistent association was found between the occurrence of single-seeded fruits (peaberries) and the direction or type of interspecific pollination. Thus, in addition to genetic implications, the results of this study can also provide agronomic implications. ABSTRAK Penyerbukan antar spesies kopi Arabika (Coffea arabica L.) dengan spesies kerabat yang bersifat diploid diduga berpengaruh terhadap karakteristik buah dan biji. Untuk mengetahui pengaruh tersebut dilakukan kombinasi penyerbukan buatan antar spesies yang dibudidayakan: C. arabica × C. canephora (A×C) dan C. arabica × C. liberica (A×L) serta kombinasi persilangan resiprokal (C×A) dan (L×A). Sebagai pembanding juga dilakukan penyerbukan dalam spesies C. arabica (A), C. canephora (C), dan C. liberica (L). Karakter morfometrik yang diamati meliputi bobot buah, panjang buah, lebar buah, tebal buah, volume buah, jumlah biji per buah, serta abnormalitas buah dan biji. Nilai tengah hasil penyerbukan antar spesies kopi kemudian dibandingkan dengan penyerbukan dalam spesies menggunakan uji t. Hasil penelitian menunjukkan penyerbukan antar spesies dengan ekses maternal (A×C dan A×L) mengakibatkan bobot dan ukuran buah nyata lebih kecil dibandingkan hasil penyerbukan dalam spesies (A×A). Di sisi lain, penyerbukan antar spesies, baik dengan ekses maternal (A×C dan A×L) maupun paternal (C×A dan L×A), menyebabkan persentase buah hampa jauh lebih tinggi dibandingkan penyerbukan dalam spesies (A×A, C×C, dan L×L). Namun, tidak terlihat adanya keterkaitan antara persentase buah berbiji tunggal (peaberry) dengan kombinasi penyerbukan antar spesies. Dengan demikian, selain implikasi genetis, hasil penelitian ini juga dapat memberikan implikasi agronomis. Kata kunci: Antar-ploidi, Hambatan antar-spesies, Kegagalan endosperma, Pasca-sigotik